Development of Community Health Care Networks Utilizing Local Community Centers - Eiichiro Ichiishi (Archives of Community Medicine and Public Health - Peertechz Publications, 2016)
Objectives: Japan is expected to become the fi rst super-aging society in the world, and the collapse of the Japanese health care system is becoming a real possibility, due to the aging of the society combined with a signifi cant increase in medical expenditure. In Japan, with the majority of land covered by forests, regional disparities between urban and depopulated mountainous areas are becoming greater each year. The importance of health management of the elderly living in these mountainous areas and diseaseprevention measures for them has been noted. Methods: In the present study, Kitanakagusuku Village and Nanjo City in Okinawa Prefecture were selected as models, and an ICT (Information and Communication Technology) -based community health care network was developed utilizing local community centers, with the aim of promoting the health of the villagers, improving the quality of their lives, and revitalizing the local communities. Results: Briefi ngs and health classes held between June 2009 and March 2010 were attended by 196 and 232 local residents, respectively. The portal website was visited by 1,200 people each month. All who had consulted physicians regarding their health and medical care were satisfi ed with the consultation services. Conclusions: In this context, a project was introduced for the development of an ICT-based community health care network that uses local community centers as bases for regional communities, focusing on examples of activities implemented in mountain villages in Okinawa Prefecture. Although this project is still a pilot trial, it is expected to signifi cantly help to improve health care systems in developing countries, as well as mountain villages and rural areas in Japan and other developed countries.